2008
DOI: 10.1124/dmd.107.019075
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Oxidase-Catalyzed Metabolism of N1-Methylnicotinamide in Vivo and in Vitro in Chimeric Mice with Humanized Liver

Abstract: ABSTRACT:Aldehyde oxidase-mediated oxidation of N 1 -methylnicotinamide to N 1 -methyl-2-pyridine-5-carboxamide (2-PY) and N 1 -methyl-4-pyridone-5-carboxamide (4-PY) in chimeric mice constructed by transplanting human hepatocytes into urokinase-type plasminogen activator-transgenic severe combined immunodeficient mice was examined in vivo and in vitro. The activity in liver cytosol of chimeric mice with a high replacement index was approximately 4-fold higher than that in control mice. Furthermore, the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…In those reports, it was demonstrated that isoforms of P450 and phase II enzymes in chimeric mouse liver behaved similarly to those in human liver in in vitro experiments. In a recent study, we showed that aldehyde oxidase in chimeric mice functions as a human-type aldehyde oxidase in vivo and in vitro (Kitamura et al, 2008). In this study, we extended the studies in chimeric mice to in vivo and in vitro metabolism of S-warfarin by CYP2C9.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In those reports, it was demonstrated that isoforms of P450 and phase II enzymes in chimeric mouse liver behaved similarly to those in human liver in in vitro experiments. In a recent study, we showed that aldehyde oxidase in chimeric mice functions as a human-type aldehyde oxidase in vivo and in vitro (Kitamura et al, 2008). In this study, we extended the studies in chimeric mice to in vivo and in vitro metabolism of S-warfarin by CYP2C9.…”
Section: Discussionmentioning
confidence: 83%
“…They also showed that the chimeric mice are a useful animal model to estimate the inductive effect on P450 in humans (Katoh et al, 2005b). We have shown that aldehyde oxidase, a cytosolic drugmetabolizing enzyme, in chimeric mice has functional characteristics almost identical to those of human aldehyde oxidase (Kitamura et al, 2008). Furthermore, Nishimura et al (2005) reported that hepatocytes from chimeric mice with nearly completely humanized liver are a useful tool for screening the potency of new drugs to induce drug-metabolizing enzymes in human.…”
mentioning
confidence: 93%
“…These mice are transplanted with approximately 80% of human hepatocytes, and the expression levels and activities of P450 and non-P450 in the liver of h-PXB mice are similar to those of humans (Katoh et al, 2004(Katoh et al, , 2005Nishimura et al, 2005;Katoh and Yokoi, 2007;Kitamura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The expression and activity of AO in liver of h-PXB mice have been reported (Kitamura et al, 2008). In contrast, the AO activity of r-PXB mice seems to be low, probably because rat hepatocytes for r-PXB mice were derived from Crj:SD rats, which show lower AO activity than other strains of rats (Moriyasu et al, 2006;Sugihara et al, 2006;Itoh et al, 2007).…”
Section: Discussionmentioning
confidence: 91%